Physicochemical Characteristics of River Water Downstream of a Large Tropical Hydroelectric Dam. (28th August 2016) - Ling, Teck-Yee; Soo, Chen-Lin; Heng, Teresa Lee-Eng; Nyanti, Lee; Sim, Siong-Fong; Grinang, Jongkar
Abstract : Water quality in the downstream river of a hydroelectric dam may be affected by the structural design and operation. To date, little is known about the water quality downstream of the largest dam in Malaysia, the Bakun hydroelectric dam. Therefore, the objective of the study was to determine the water quality downstream of the dam when the spillway was closed and when it was opened. Results of the study indicate that the dam plays a significant role in regulating the water quality downstream of it. When the spillway was closed, pH and oxygen were lower in the river where DO was below 5 mg/L. When the spillway was opened, the water quality improved in terms of oxygen content (>8.0 mg/L), total sulphide (TS), and chemical oxygen demand (COD) but deteriorated in terms of five-day biochemical oxygen demand (BOD5 ), total ammonia nitrogen (TAN), and total phosphorus (TP). Additionally, the intensity of the impacts, particularly BOD5, COD, and TAN, shows a declining trend as distance from the dam increases. This study shows that impacts on the water quality extend to a distance of 32 km from the dam particularly turbidity and DO and opening the spillway changes the water quality significantly.